Distribuição da heterocromatina em representantes do gênero Solanum Lindl. (Solanaceae) do Nordeste Brasileiro - Carneiro, Sócrates Torres (2015)
Solanaceae A. Juss. has about 2500 species and 100 genera, with cosmopolitan distribution. The family presents remarkable economic importance, with several species cultivated for food. Solanum Lindl, the most representative genus of the family, has about 1400 species and problematic taxonomy, according to this high diversity. The aim of this paper was to analyze, by using double staining with the fluorochromes CMA and DAPI, the heterochromatin distribution in 16 representatives of the genus Solanum in Northeast Brazil, as well as four species of Solanaceae as outgroups. The chromosome numbers ranging from 2n = 20 in Schwenckia americana L., 2n = 22 in Brunfesia uniflora Pohl. D. Don., 2n = 24 for all representatives of the genus Solanum, 2n = 26 in Metternichia princeps Mik., to 2n = 48 in Physalis angulata L., the former being a tetraploid species. In all karyotypes there were predominantly metacentric and submetacentric chromosomes, with the occurrence of acrocentric pairs in Solanum. The average chromosome size ranging from 1,43 μm in S. asterophorum Mart. to 5.99 μm in S. palinacanthum Dunal. The intrachromosomal asymmetry index (A1) ranging from 0.18 in S. jabrense Agra. to 0.51 in S. palinacanthum Dunal., while the interchromosomal asymmetry (A2) ranging from 0.09 in S. jabrense Agra. to 0.23 in S. paraibanum Agra. In most species were observed terminal CMA+ /DAPI−/0 heterochromatic bands, punctiforms or forming a small block, sometimes associated with NORs or forming satellites. Solanum palinacanthum Dunal. presented intestitial CMA+ /DAPI−/0 bands. DAPI+ /CMA−/0 terminal bands were observed in S. capsicoides All., S. paludosum Moric., S. polytrichum Moric. and S. rhytidoandrum Sendtn. According to the different types of bands observed in Solanum species, it is possible that four different chromosome lineages have evolved independently within the genus. The occurrence of CMA+ /DAPI− bands associated with NORs, as well as the basic number x = 12, probably are the most ancient characters for the genus Solanum.